Strengthening Pengejaran Tourism Village through the Design of a Sustainable, Tourism-Based Information Centre in Kintamani - I Kadek Merta Wijaya; I Wayan Jawat; I Made Surya Kumara (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Pengejaran Village in Kintamani District has significant natural and cultural potential. It can be developed as a community-based tourist village. However, realizing this potential faces substantial limitations in tourism support facilities, particularly regarding destination information provision and promotion of local resources. This research aims to strengthen Pengejaran Tourism Village development through the design of an Information Center to serve as an information hub and promotional space for the village's potential. The methodology employed includes field observations, interviews with community members and village officials, focused group discussions (FGD), and digital-based architectural design planning. The research findings demonstrate that the village center area holds a strategic position suitable for development as a gateway to village tourism activities. The Information Center design accommodates multiple functions, including a tourism information center, village potential gallery, MSME product promotion space, cultural performance venue, and public open space . Sustainable architecture principles are applied through optimized natural lighting, cross-ventilation, the use of local materials, and the integration of the building with open spaces. The design incorporates elements of Balinese vernacular architecture based on the Tri Hita Karana philosophy to maintain balance among humans, the environment, and local cultural values Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and Production